2018
DOI: 10.1016/j.jaci.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Human TH17 cell development requires processing of dendritic cell–derived CXCL8 by neutrophil elastase

Abstract: Polymorphisms related to ORMDL3 are associated with asthma susceptibility, alterations in transcriptional regulation of ORMDL3, and changes in TH2 cytokine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 16 publications
8
62
0
Order By: Relevance
“…Moreover, GM‐CSF and/or IFN‐γ derived from Th17 cells were shown to promote neutrophil survival as well as enhance various neutrophil effector functions . More recently, neutrophil‐derived elastase has been shown to process dendritic cell‐derived CXCL8 into a truncated, potent Th17 cell‐inducing form . Our current data on the ability of TLR8‐activated neutrophils to also drive via IL‐23 the differentiation of Th17 cells, is consistent with another study showing that Group B Streptococcus (GBS)‐stimulated neonatal neutrophils induce robust Th1‐ and Th17‐type responses in neonatal CD4 + T cell and Treg populations through mechanisms involving cell‐cell contact and soluble mediators, adding new knowledge on the regulation and activation of the neutrophil/Th17 cell crosstalk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, GM‐CSF and/or IFN‐γ derived from Th17 cells were shown to promote neutrophil survival as well as enhance various neutrophil effector functions . More recently, neutrophil‐derived elastase has been shown to process dendritic cell‐derived CXCL8 into a truncated, potent Th17 cell‐inducing form . Our current data on the ability of TLR8‐activated neutrophils to also drive via IL‐23 the differentiation of Th17 cells, is consistent with another study showing that Group B Streptococcus (GBS)‐stimulated neonatal neutrophils induce robust Th1‐ and Th17‐type responses in neonatal CD4 + T cell and Treg populations through mechanisms involving cell‐cell contact and soluble mediators, adding new knowledge on the regulation and activation of the neutrophil/Th17 cell crosstalk.…”
Section: Discussionsupporting
confidence: 89%
“…48 More recently, neutrophil-derived elastase has been shown to process dendritic cell-derived CXCL8 into a truncated, potent Th17 cell-inducing form. 49 Our data greatly extend previous observations on the ability of human neutrophils to express/produce IL-23. For example, it was previously shown that, while Helicobacter pylori Neutrophil Activating Factor triggers the expression of IL-23p19 mRNA by human neutrophils, 51…”
Section: Discussionsupporting
confidence: 86%
“…1 The importance of neutrophils in the HS pathogenesis is underlined by the increased levels of CXCL-8 that can be cleaved by neutrophil elastase to activate Th17 cells to produce bioactive IL-17. 7 Some previously published results, that showed significant upregulation of TNF-α, IL-1ß, and IL-10 in (peri)lesional HS skin, could not be confirmed statistically. 8,9 This can be explained by the different approaches as in our study biopsies were homogenized for in situ assessment, while van der Zee et al and Kelly et al cultured the skin biopsies for, respectively, 24 and 3 hours.…”
mentioning
confidence: 84%
“…Neutrophils are now known to be involved in orchestrating adaptive immune responses by influencing various cell types, either by releasing multiple soluble mediators or via direct cellular contacts. For instance, neutrophils can modulate DC migration, maturation, and their CD4 + T cell polarizing capacity [ 2 , 80 ]. In addition, they can suppress or enhance B cell, CD4 + T cell, and γδ T cell functions (independent of MHC), or even act as antigen-presenting cells under specific activating conditions and thereby drive antigen-specific T cell responses [ 10 , 79 ].…”
Section: Neutrophilsmentioning
confidence: 99%